2003
DOI: 10.2337/diacare.26.9.2505
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcome of a Combination of Weight Loss Therapies for Subjects With Type 2 Diabetes

Abstract: OBJECTIVE -The purpose of this study was to evaluate the effects of a combination weight loss program using intermittent low-calorie diets, energy-controlled meal replacement products, and sibutramine on weight loss, diabetes control, and cardiovascular risk factors in overweight or obese subjects with type 2 diabetes.RESEARCH DESIGN AND METHODS -Overweight or obese individuals with type 2 diabetes treated with diet or oral medication were randomly assigned to either a standard therapy or combination therapy g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…As previously reported, the S/C therapy group lost little weight during year 1 of standard therapy (15). After starting combination therapy at the beginning of year 2, this group demonstrated a pattern of weight loss similar to that observed during year 1 in the C therapy group.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…As previously reported, the S/C therapy group lost little weight during year 1 of standard therapy (15). After starting combination therapy at the beginning of year 2, this group demonstrated a pattern of weight loss similar to that observed during year 1 in the C therapy group.…”
Section: Discussionsupporting
confidence: 83%
“…We have previously reported that this combination program for weight loss produced significantly more weight loss and improved diabetes control compared with a standard weight loss program at 1 year (15). We now report that subjects who followed the combination therapy program for 2 years maintained significant weight loss of 4.6 kg and had a decrement in HbA 1c of 0.5%.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…1 The components of the duodenal pacer BBALANCE system^: left implantable pulse generator (IPG) and bipolar lead with two electrodes; right remote control and laptop Fig. 2 The two BALANCE system leads attached to the duedenum wall [23]. It is therefore likely that further effects of duodenal stimulation are responsible for the metabolic effect.…”
Section: Discussionmentioning
confidence: 99%